Repurchase Agreement: Dual Perspectives in Indonesian Income Tax Law - Indradi (Yayasan Ilomata, 2023)
There are two fundamental issues of taxing repo based on Indonesian Income Tax Law. First, there is no specific tax law addressing repo transaction and second, Indonesia applies hybrid income tax system, global and schedular income tax. This paper aims to describes and analyses two perspectives, the global dan schedular system, of taxing repo based on Indonesian Income Tax Law. From legal perspective, a repo is taxed under schedular income tax system where it views a repo as two transactions. Meanwhile, from economic perspective, a repo is viewed as a single transaction that is based on comprehensive income tax system. Although, prevailing law principle favors the first perspective, the latter is logically more sensible and far more equitable than the first. Regulatory measures based on a comprehensive income tax system are needed to resolve the dispute.